Issues in health and health care related to race/ethnicity, immigration, SES and gender - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2012)
The 30th Anniversary volume of Research in the Sociology of Health Care looks at the important links between major social factors and health and health care. The four main factors examined in the book are race/ethnicity, immigration, Socioeconomic Status (SES) and gender. Starting with an introductory chapter which reviews some of the important sociological literature on these social factors as linked to health, the book goes on to cover various key issues, including obesity, ageing, immigration and racial segregation.